Paving the path: a design team’s perceptions on the use of open design practices - Benedet, Lara Souza; Gonçalves, Berenice Santos; Cunha, Cristiano José Castro de Almeida; da Silva, Solange Maria (DAT Journal, 2024)
This article aimed to understand the perceptions of a design team regarding the use of open design practices. To this end, after a brief review of open design and open design practices, interviews were carried out with members of the design team of an extension project focused on the production of open educational resources within the scope of professional and technological training. The project dynamics and the open practices adopted are addressed, in order to explain the context in which the interviewees are inserted, and consequently, some of their prior knowledge on the topic. The results show that designers see several potentialities in open design practices, however they also encounter some limitations, such as the difficulty in searching for images with an open license and the lack of knowledge regarding open software, mainly due to the lack of information on the topic to be discussed at your disposal.